RNA Interference and Nanotechnology: A Promising Alliance for Next Generation Cancer Therapeutics - Swaminathan, Guruprasadh; Shigna, Aisha; Kumar, Aviral; Byroju, Vishnu Vardhan; Durgempudi, Varsha Reddy; Dinesh Kumar, Lekha (Frontiers in Nanotechnology, 2021)
Cancer is a significant health hazard of the 21st century, and GLOBOCAN predicts increasing cancer incidence in the coming decades. Though several conventional treatment modalities exist, most of them end up causing off-target and debilitating effects, and drug resistance acquisition. Advances in our understanding of tumor molecular biology offer alternative strategies for precise, robust, and potentially less toxic treatment paradigms for circumventing the disease at the cellular and molecular level. Several deregulated molecules associated with tumorigenesis have been developed as targets in RNA interference (RNAi) based cancer therapeutics. RNAi, a post-transcriptional gene regulation mechanism, has significantly gained attention because of its precise multi-targeted gene silencing. Although the RNAi approach is favorable, the direct administration of small oligonucleotides has not been fruitful because of their inherent lower half-lives and instability in the biological systems. Moreover, the lack of an appropriate delivery system to the primary site of the tumor that helps determine the potency of the drug and its reach, has limited the effective medical utilization of these bio-drugs. Nanotechnology, with its unique characteristics of enhanced permeation and better tumor-targeting efficiency, offers promising solutions owing to the various possibilities and amenability for modifications of the nanoparticles to augment cancer therapeutics. Nanoparticles could be made multimodal, by designing and synthesizing multiple desired functionalities, often resulting in unique and potentially applicable biological structures. A small number of Phase 1 clinical trials with systemically administered siRNA molecules conjugated with nanoparticles have been completed and the results are promising, indicating that, these new combinatorial therapies can successfully and safely be used to inhibit target genes in cancer patients to alleviate some of the disease burden. In this review, we highlight different types of nano-based delivery strategies for engineering Nano-RNAi-based bio drugs. Furthermore, we have highlighted the insights gained from current research that are entering the preclinical evaluation and information about initial clinical developments, shaping the future for next generation cancer therapeutics.